Identification of potent human neutralizing antibodies against SARS-CoV-2 implications for development of therapeutics and prophylactics - Shaojuan Zhao (Nature Portfolio, 2021)
Applying neutralizing antibodies against SARS-CoV-2 to infected patients is a promising anti-viral treatment strategy. Here, Zhao et al. derive RBD-targeting monoclonal antibodies from a naïve human phage-displayed Fab library and show their  prophylactic and therapeutic potential in hACE2-transgenic mice.